The last word [large type] - Lutz, Lisa (Lutz, Lisa. Spellman novel., 2013)
Izzy's troubles are just beginning. After her hostile takeover of Spellman Investigations, Izzy's parents simply go on strike. Her sister, Rae, comes back into the family business with questionable motivations. Her other employees seem to be coping with anxiety disorders, and she has no idea how to pay the bills. However, her worst threat comes from someone who is no relation. Within months of assuming control of the business, Izzy is accused of embezzling from a former client, the ridiculously wealthy Mr. Slayter, who happens to have Alzheimer's, which Izzy and he are diligently trying to keep under wraps. Not only is Slayter's business and reputation on the line, but if Izzy gets indicted for embezzlement, she'll lose everything -- her business, her license, and her family's livelihood. Is this the end of Izzy Spellman, PI?